Effect of growing media on growth and flowering of gerbera (Gerbera jamesonii) cultivars under naturally ventilated polyhouse - SAIKIA, SEWALI; TALUKDAR, MADHUMITA CHOUDHURY; MAHANTA, PRADIP (The Indian Journal of Agricultural Sciences, 2016)
The performance of gerbera (Gerbera jamesonii Bolus ex Hooker F.) cultivars were evaluated in different growing media in naturally ventilated polyhouse during 2012-13 to 2013-14. Three varieties, viz. Batavia, Faith and Antibes were grown on five different growing media, i.e. partially decomposed rice husk, vermicompost, enriched compost, soil based biofertilizer and control. Growth, flowering and physiological characters were evaluated. The cultivar Antibes was found to be superior with respect to number of leaves/plant (34.57), leaf area index (1.73), net assimilation rate (0.059mg/cm2/day), leaf area duration (55.98 LAI days) and vase life (9.37 days). Among the five growing media evaluated; growth, flowering and physiological characters were better in enriched compost. Number of leaves/plant (36.74), leaf area index (1.86), total chlorophyll content (0.246 mg/g), net assimilation rate (0.064 mg/cm2/day), leaf area duration (58.94 LAI days), days to flower bud visibility (79.18 days), days to full bloom (17.41 days), number of flowers/plant (12.05), diameter of flower (10.29 cm), length of flower stalk (57.47 cm), diameter of flower stalk (0.75 cm) and vase life (10.89 days) of flower were found to be highest for enriched compost.